EFEKTIVITAS PENGGUNAAN MEDIA KARTU HILANG (KAHI) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VI SD - Kirana, Rara Netra Ihya; Sumaji, Sumaji; Ermawati, Diana (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2023)
The low mathematics learning outcomes of class VI students at SD 3 Purwosari is due to the fact that learning is still teacher-centered and has not utilized learning media so that effective and appropriate solutions and innovations are needed so that mathematics learning achieves the expected learning objectives. One of the innovations that can be applied to learning mathematics is the use of KAHI  media. The aims of this study were 1) to examine the differences before and after applying KAHI media to students' mathematics learning outcomes, 2) to find out the increase in students' mathematics learning outcomes before and after applying KAHI Media. This research is a quantitative research type of pre-experimental design using one group pretest-posttest. The hypothesis test used is the Paired Sample t Test and the N-Gain test. The results of the Paired Sample t Test obtained a significance value of 0.000<0.05 indicating that there was a significant difference between learning before and after applying the KAHI media. The results of the N-Gain test obtained 45% results in the medium category, so it can be concluded that the use of KAHI media is effective for the mathematics learning outcomes of grade VI elementary school students.